KAJIANEKOLOGISPASIALBENTANGLAHANUNTUKKELESTARIANSITUSSEJARAHDIKECAMATANIMOGIRIDANKRETEKKABUPATENBANTUL - Khotimah, Nurul (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2015)
Landscapeecologyapproachisneededtoinventarizedthehistoricsite,environmentalproblemthatbemakemanagementconstraint,regionpotention,alsodirectionandmanagementpriority,anddevelopmentofhistoricsitesaspopulartourismarea. Theresultoftheresearchshowsthat:(1)HistoricsitesatImogiriDistrictspreadatGirirejo,Wukirsari,Karangtengah,Selopamioro,andImogiriVillages,meanwhileatKretekDistrictgatheringroupatParangtritisVillage;(2)WholelandstatusofhistoricsitesmeansSultangroundlandstatus,withlandprocessingthatisdonebyaroundcommunityforfield,communityforest,miningofCdiggingmaterial,housing,homestay,shop/smallshopthatcanmakethreatenhistoricsitescontinuitythatexist;(3)Theproblemsofenvironmentaroundhistoricsitescanbephysicalandsocialenvironment;and(4)Foranticipatingitneedsmakinghistoricsitescontinuityorganizationorinstitutiontoorganizeandsupportedecosystemapproachastheefforttorganizeanddevelopedthehistoricsitesaspopulartourismplaces. KeyWord:spatialecology,historicsites,continuity